Efficacy and safety of caudal dexmedetomidine in pediatric infra-umbilical surgery: a meta-analysis and trial-sequential analysis of randomized controlled trials. Issue 5 (15th January 2021) - Shah, Ushma Jitendra; Nguyen, Derek; Karuppiaah, Niveditha; Martin, Janet; Sehmbi, Herman
Abstract : Background: Dexmedetomidine is used as a local-anesthetics adjuvant in caudal block to prolong analgesia in pediatric infra-umbilical surgery. Objective: We evaluated the analgesic efficacy and safety of the addition of caudal dexmedetomidine to local anesthetics (vs local anesthetics alone) in pediatric infra-umbilical surgery. Evidence review: We searched 10 databases for randomized controlled trials (RCTs) of pediatric patients undergoing infra-umbilical surgery, comparing caudal block with and without dexmedetomidine as local anesthetic adjuvant. We performed a frequentist random-effects meta-analysis (R statistical package). We analyzed continuous outcomes as a ratio of means (ROM) and dichotomous data as relative risk (RR), along with 95% CI. We included 19 RCTs (n=1190 pediatric patients) in the meta-analysis. The primary outcome was duration of analgesia (defined as 'the time from caudal injection to the time at which the study-specific pain score was greater than a cut-off threshold'). Findings: Data from 19 included RCTs (n=1190) suggested that compared with control (mean duration 346 min), the addition of caudal dexmedetomidine significantly prolonged the duration of analgesia (ratio of means 2.14, 95% CI 1.83 to 2.49, p<0.001; 'moderate' evidence). Trial-sequential analysis showed adequate 'information size' for the primary outcome. Caudal dexmedetomidine also reduced the number of analgesic administrations ('low' evidence), total acetaminophen dose ('moderate' evidence) and the risk of emergence delirium ('moderate' evidence). There were no significant differences in adverse effects such as hypotension, bradycardia, post-operative nausea and vomiting, urinary retention and respiratory depression. Conclusions: Our results suggest that the addition of dexmedetomidine to local anesthetic in caudal block significantly improves the duration of analgesia and reduces the analgesic requirements, while maintaining a similar risk-profile compared with local anesthetic alone. Further data on neurological safety are needed.